Helicobacter pylori colonization and obesity – a Mendelian randomization study. Issue 1 (December 2017) - den Hollander, Wouter; Broer, Linda; Schurmann, Claudia; Meyre, David; den Hoed, Caroline; Mayerle, Julia; Hofman, Albert; Homuth, Georg; Uitterlinden, André; Lerch, Markus; Kuipers, Ernst
Abstract Obesity is associated with substantial morbidity, costs, and decreased life expectancy, and continues to rise worldwide. While etiological understanding is needed for prevention, epidemiological studies indicated that colonization withHelicobacter pylori (H .pylori) may affect body mass index (BMI), but with inconsistent results. Here, we examine the relationship betweenH .pylori colonization and BMI/obesity. Cross-sectional analyses were performed in two independent population-based cohorts of elderly from the Netherlands and Germany (n = 13, 044). Genetic risk scores were conducted based on genetic loci associated with eitherH .pylori colonization or BMI/obesity. We performed a bi-directional Mendelian randomization. Meta-analysis of cross-sectional data revealed no association between anti-H .pylori IgG titer and BMI, nor ofH .pylori positivity and BMI. Anti-H .pylori IgG titer was negatively associated with obesity (OR 0.99972; 95% CI 0.99946-0.99997, p = 0.03) and with obesity classes (Beta −6.91 10−5 ; 95% CI −1.3810−4, −5.4910−7, p = 0.048), but the magnitude of these effects was limited. Mendelian randomization showed no causal relation betweenH .pylori genetic risk score and BMI/obesity, nor between BMI or obesity genetic risk scores andH .pylori positivity. This study provides no evidence for a clinically relevant association betweenH .pylori and BMI/obesity.